TIDAK ADA PERBEDAAN ANTARA PERMAINAN FINGER PAINTING DAN MERONCE DALAM MENINGKATKAN MOTORIK HALUS PADA ANAK USIA PRASEKOLAH DI PENDIDIKAN ANAK USIA DINI KOTA DENPASAR - I Nyoman Ari Suryawan; Ari Wibawa; I Putu Adiartha Griadhi (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
Finger Painting and meronce could enhance fine motor in children aged 4-6 years. Children in this period was good physical or psychological development. This study aimed to find out difference of finger painting and meronce to improved fine motor development of preschool children in early childhood in Denpasar. This study used Quasy Experimental Design with pre and post test with control Group Design. The samples were divided into three groups with 14 children each group. The sampling technique was random sampling. Statistical test used one-way ANOVA. The results obtained p = 0,000 (p <0.05) which showed no difference between playing finger painting and meronce to improve motor development of preschool children. This study showed between finger painting and meronce were effective to improve motor development of preschool children with p = 0.192 in LSD post hoc test. The conclusion ofthis study was Finger Painting Game can enhance the fine motor development of preschoolers. Meronce game could enhance fine motor development of preschoolers. Finger Painting and Meronce games were equally effective on improving fine motor of preschoolers. The results of this study could be useful to stimulate the fine motor developmentof preschool children. Key Words: Finger Painting, Meronce, fine motor